Role of Multiparametric MRI in the Diagnosis of Prostate Cancer: Update. Issue 2 (April 2016) - Rosi, Giovanni; Indino, Elena Lucia; Salvo, Vincenzo; Colarieti, Anna; Fierro, Davide; Scialpi, Michele; Panebianco, Valeria
Prostate cancer is the most common malignancy of the male gender. The role of magnetic resonance imaging has evolved very rapidly over the years to be currently recognized as a fundamental tool in the diagnosis, treatment and follow-up of prostate cancer.